Penerapan Sanksi Hukum Terhadap Narapidana Pelanggar Tata Tertib Terkait Pemberian Hak - Setyawati, Dewi; Sudarmanto, Kukuh; Arifin, Zaenal; Subiadi, Rilda (Journal Juridisch, 2024)
This research aims to analyze the obstacles and supporting factors in the application of legal sanctions against inmates who violate the order related to the granting of rights in Class II A Penitentiaries Semarang. This is important to study considering that there are still violations of inmates' rights in some prisons in Indonesia. This research is a normative-empirical legal research, with a statutory approach. The novelty of this research is that there are changes in the statutory regulations and in the research location there is an increase in the number of offenders. The results of the study show that the limited capacity and density of prisons make implementing regulations more difficult. Discomfort and poor detention conditions create tensions and violations of inmates' rights. Meanwhile, the imposition of strict sanctions sometimes violates the rights of inmates which is also a problem for prison officers, referring to a comparison of data on the number of disciplinary offenders from the previous year at Semarang Class II Prison has not experienced significant changes. This means that the number of offenders continues to increase and there are still inmates who repeat their crimes. The obstacles in the application of legal sanctions against inmates who violate the statutory regulations in Semarang Class IIA Penitentiary include limited resources, density or overcapacity, resistance or resistance from inmates, and lack of external supervision. While the solutions are preventive efforts and repressive efforts. Penelitian ini bertujuan untuk menganalisis kendala dan faktor pendukung dalam penerapan sanksi hukum terhadap narapidana yang melanggar tata tertib terkait pemberian hak di Lapas Kelas II A Semarang. Hal ini menjadi penting untuk diteliti mengingat masih terdapat pelanggaran terhadap hak-hak narapidana di beberapa Lapas di Indonesia. Penelitian ini adalah penelitian hukum normatif-empiris, dengan pendekatan perundang-undangan. Kebaruan dari penelitian ini adalah terdapat dari sisi perubahan peraturan perundang-undangan dan pada tempat penelitian yang terdapat peningkatan jumlah pelanggar. Hasil penelitian menunjukkan terbatasnya kapasitas dan kepadatan penjara membuat peraturan pelaksanaan menjadi lebih sulit. Ketidaknyamanan dan kondisi penahanan yang buruk menciptakan ketegangan dan pelanggaran hak-hak narapidana. Sementara itu, pemberian sanksi yang tegas terkadang melanggar hak-hak narapidana yang juga menjadi permasalahan bagi petugas pemasyarakatan, mengacu pada perbandingan data jumlah pelanggar disiplin dari tahun sebelumnya di Lapas Kelas II Semarang tidak mengalami perubahan signifikan. Artinya, jumlah pelanggar masih terus bertambah dan masih terdapat narapidana yang mengulangi kejahatannya. Kendala dalam penerapan sanksi hukum terhadap narapidana yang melanggar peraturan perundang-undangan di Lapas Kelas II A Semarang antara lain adalah keterbatasan sumber daya, kepadatan atau kelebihan kapasitas, resistensi atau perlawanan dari narapidana dan kurangnya pengawasan dari luar. Sedangkan solusi yang dilakukan adalah upaya preventif dan upaya represif.